A reduced-complexity shoreline change model combining longshore and cross-shore processes: The LX-Shore model. (November 2018) - Robinet, Arthur; Idier, Déborah; Castelle, Bruno; Marieu, Vincent
Abstract: A reduced-complexity numerical model, LX-Shore, is developed to simulate shoreline evolution along wave-dominated sandy coasts. The model can handle any sandy shoreline geometries (e.g. sand spits, islands), including non-erodible areas such as coastal defenses and headlands, and is coupled with a spectral wave model to cope with complex nearshore wave fields. Shoreline change is primarily driven by the gradients in total longshore sediment transport and by the cross-shore transport owing to variability in incident wave energy. Application to academic cases and a real coast highlights the potential of LX-Shore to simulate shoreline change on timescales from hours (storm) to decades with low computational cost. LX-Shore opens new perspectives in terms of knowledge on the primary mechanisms locally driving shoreline change and for ensemble-based simulations of future shoreline evolution. Highlights: A new shoreline change model is developed for wave-dominated sandy coasts: LX-Shore. The numerical implementation allows addressing complex shoreline plan-view shapes. LX-Shore couples cross-shore and alongshore processes. LX-Shore simulates shoreline variability up to decades with low computational cost. LX-Shore can provide new insights into the mechanisms controlling shoreline change.